Endourological Management of Urolithiasis in Donor Kidneys prior to Renal Transplant. (22nd June 2011) - Vasdev, Nikhil; Moir, John; Dosani, Muhammed T.; Williams, Robert; Soomro, Naeem; Talbot, David; Rix, David
Abstract : Background . We present our centres successful endourological methodology of ex vivo ureteroscopy (EVFUS) in the management of these kidneys prior to renal transplantation. Patient and Methods . A retrospective analysis was performed of all living donors (n = 157 ) identified to have asymptomatic incidental renal calculi from January 2004 until December 2008. The incidence of asymptomatic renal calculi was 3.2% (n = 5 ). Donors were subdivided into 2 groups depending on whether theydonated the kidney with the renal calculus (Group 1) versus the opposite calculus-free kidney (Group 2). Results . All donors in Group 1 underwent a left laparoscopic donor nephrectomy. The calculi were extracted in all 3 cases using a 7.5 Fr flexible ureteroscope either prior to transplant (n = 2 ) or on revascularization (n = 1 ). There were no urological complications in either group. At a mean followup at 64 months there was no recurrent calculi formation in the recipient in Group 1. However, 1 recipient formed a calculus in group 2 at a follow up of 72 months. Conclusions . Renal calculi can be successfully retrieved during living-related transplantation at the time of transplant itself using EVUS. This is technically feasible and is associated with no compromise in ureteral integrity or renal allograft function.